Peranan Tari Batile, Tari Berburu Suku Anak Dalam Jambi untuk Meningkatkan Kreativitas Seni Siswa di Sekolah Dasar - Nabila, Nabila; Fazliani, Bella (Lembaga Yasin AlSys, 2023)
Batile Dance, a hunting dance originating from the Anak Dalam tribe in Jambi, plays a significant role in enhancing the artistic creativity of elementary school students. This dance is not only a valuable cultural heritage but also a powerful source of inspiration for the younger generation. This research aims to delve deeper into the role of Batile Dance in enriching the artistic creativity of elementary school students. The research adopts a qualitative approach with observation, interviews, and documentation as the methods. The participants in this study are elementary school students involved in Batile Dance learning activities. The research findings indicate that Batile Dance has a significant influence in enriching the artistic creativity of elementary school students. Through practicing this dance, students can develop their imagination, enhance their motor skills, and sharpen their ability to express themselves artistically. Batile Dance also provides opportunities for students to learn cultural values, local wisdom, and respect for nature. In the context of art education in elementary schools, Batile Dance can be integrated into the curriculum to enrich students' art experiences. Teachers can utilize this dance as an engaging learning tool, involving students in the creative process and fostering curiosity and exploration in art. Thus, Batile Dance has the potential to greatly contribute to the development of artistic creativity among elementary school students.